Media Komunikasi Visual Awareness Campaign Pengetahuan Seksualitas Pada Anak-Anak Sejak Dini di Kota Palembang - Allya Syahrani; Yosef Yulius; Hestia Lubis (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Sexuality is a important aspect of human growth, including physical, emotional, social, and psychological elements. In Indonesia, sexuality is a culturally delicate and frequently taboo topic, especially regarding the education of children. Numerous parents find it challenging to tackle the subject, worrying it could spark early curiosity or be seen as unsuitable for their child's age. Methods based on fear and restrictions frequently do not connect with children in a meaningful way, while those guided by developmental psychology like the theories of Piaget and Freud tress the importance of age-appropriate, logical conversation. The absence of precise information from families and schools drives children to look for knowledge from media or friends, which can reinforce misinformation. Worrying levels of sexual violence targeting children, especially in regions such as Palembang, highlight the need for thorough, ethically-based sexuality education. The problem addressed in this design project is how to develop a visual communication medium for an awareness campaign on early childhood sexuality education in Palembang City using the design thinking method. The outcome of this project is a set of visual communication media in the form of an awareness campaign on sexuality education, which is expected to provide educational value for children from an early age